2017
DOI: 10.1039/c7ta02109g
|View full text |Cite
|
Sign up to set email alerts
|

A type-II GeSe/SnS heterobilayer with a suitable direct gap, superior optical absorption and broad spectrum for photovoltaic applications

Abstract: Type-II band alignment, a suitable direct gap (1.519 eV), superior optical-absorption (∼105) and a broad spectrum make the GeSe/SnS heterobilayer a promising material for photovoltaic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 50 publications
3
72
0
Order By: Relevance
“…Its large absorption coefficient ($10 5 cm À1 ), 9,10 as well as the predicted high carrier mobility, 7 renders it a great of potential applications in optoelectronic and electronic devices. 2,4,[11][12][13][14][15][16][17][18] Moreover, similar to the black phosphorous (BP) with puckered honey-comb crystal structure, SnS also possesses anisotropic electronic, 19,20 thermoelectric, [21][22][23] piezoelectric 24 and optical 25,26 properties. Given the strongly anisotropic properties of SnS, the SnS-SnS x Se 1Àx core-shell heterostructure with anisotropic photoresponse and the SnS-based photodetector with highly anisotropic performance of near-infrared have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Its large absorption coefficient ($10 5 cm À1 ), 9,10 as well as the predicted high carrier mobility, 7 renders it a great of potential applications in optoelectronic and electronic devices. 2,4,[11][12][13][14][15][16][17][18] Moreover, similar to the black phosphorous (BP) with puckered honey-comb crystal structure, SnS also possesses anisotropic electronic, 19,20 thermoelectric, [21][22][23] piezoelectric 24 and optical 25,26 properties. Given the strongly anisotropic properties of SnS, the SnS-SnS x Se 1Àx core-shell heterostructure with anisotropic photoresponse and the SnS-based photodetector with highly anisotropic performance of near-infrared have been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 /PtS 2 heterogeneous interfaces by the first principle methods, which has been widely used in many previous studies for bilayer structures [14,[17][18][19][21][22][23][24].…”
Section: In This Work We Design and Analyze Electronic And Optical Pmentioning
confidence: 99%
“…For example, a series of theoretical studies [5][6][7] reported that graphene/silicone heterobilayer (HBL) exhibited stronger optical absorption than silicene and graphene monolayers. More recently, germanium monochalcogenides (GeX, X = S, Se, Te) arouse widespread attention in scientific community, because of their excellent mechanical flexibility, high carrier mobility, suitable band structures as well as inherent dipoles with large difference in electronegativity [8][9][10]. Particularly, layered Germanium telluride (GeTe), has been widely investigated in various fields due to its predominate semiconducting and ferroelectric nature, such as Li-ion batteries [11] and photocatalytic water splitting [12].…”
Section: Introductionmentioning
confidence: 99%